Generation, propagation and characterization of second and full-term amniotic fluid-derived mesenchymal stem cell - Ghoraishizadeh, Peyman (2016)
Mesenchymal stem cells (MSCs) are multipotent stem cells that are highly proliferative with the ability of self-renewal and the potential to differentiate into various cell lineages. The differentiation potential, self-renewability, immunesuppression properties and ease for genetic modification make them a frontier candidate for regenerative medicine, cell and gene therapy. To date, bone marrow (BM) is the most accessible source of MSCs for isolation, but BM aspiration is very invasive and a painful procedure. Although the success rate of stem cell retrieval and their expansion is high in adult bone marrow samples, certain conditions can limit their accessibilities. For instance, in some clinical cases such as bone marrow failure, aplastic anaemia, leukaemia or chemotherapy, patients often encounter complications of inadequate cellular fractions in their bone marrow aspiration, for these patients, the only alternative source of MSCs would be a second party donor. Most of the time, there are difficulties in finding the suitable donor. Moreover, the number and differentiation capacity of MSCs decrease significantly with ageing. Altogether, these necessitate a need to search for alternative sources of MSCs for research and therapeutics application. Human amniotic fluid cells (hAFCs) have been used as a diagnostic tool for prenatal diagnosis and they have been found to be a rich source of progenitor/stem cells. Human amniotic fluid (hAF) is usually considered as clinical wastes and inevitably discarded during amniocentesis, caesarean (c-section) and normal delivery. Two main populations of stem cells that can be isolated from human amniotic fluid, are amniotic fluid mesenchymal stem cells (hAF-MSCs) and amniotic fluid stem cells. In current study hAF-MSCs are isolated from amniocentesis and caesarean samples and propagated in vitro using different growth medium. The study performed a comparative analysis for the effect of different media components on the properties of MSCs (cell morphology, cell growth, surface markers, colony forming unit assay and differentiating potential). The hAF-MSCs were the characterized using flow cytometry technique and screen a panel of cell surface markers. In conclusion, hAF-MSCs were successfully generated from the amniocentesis and cesarean amniotic fluid samples, without any significant characteristic difference between hAF-MSCs derived from the two gestation periods. XSFM was found to be the best medium for the generation and propagation of the hAF-MSCs in comparison to the DMEM-FBS and DMEM-HS. Therefore, this study suggests that the cesarean amniotic fluid, a waste product during delivery is feasible to generate xenogenic free hAF-MSCs for safe therapeutic application and possible hAF-MSCs\banking.